Rechtsfragen der Ressourcenzuteilung in der COVID-19-Pandemie – Zwischen Utilitarismus und Lebenswertindifferenz - Hübner, Joachim; Schewe, Denis M.; Katalinic, Alexander; Frielitz, Fabian-S. (DMW - Deutsche Medizinische Wochenschrift, 2020)
The COVID-19 pandemic poses unprecedented challenges for the German health care system. What is already the case in some other countries, may occur in Germany in the near future also: Faced with limited ICU resources, doctors will be forced to decide which patients to treat and which to let die. This paper examines the legal implications of such decisions. It takes up arguments from the general discussion on prioritization in medicine. A constitutional hurdle for the application of utilitarian criteria (in particular patients’ age or social role) comes from the principle that every human life is of equal value and must not be traded off against others (“life value indifference”). However, the limits that the Grundgesetz (German Basic Law) sets for state actions do not apply directly to doctors. According to the Musterberufsordnung (professional code of conduct), doctors act based on their conscience and the requirements of medical ethics and humanity. The implications of this normative standard for the prioritizing in an exceptional situation as the COVID 19 pandemic have not been sufficiently clarified. This uncertainty leads to emotional and moral burdens for doctors. The authors conclude that the German law grants a limited freedom of choice that allows physicians to apply utilitarian criteria in addition to purely medical decision algorithms.
Keywords: COVID-19-Pandemie; Behandlungspflicht; rechtfertigende Pflichtenkollision; Priorisierung